The Genetic Relationship Analysis of Genus Nomorhamphus from Lindu Lake, Central Sulawesi and Adaptive Responses to Exposure Different Light Wavelengths - Hafidah, Riva; Soelistyowati, Dinar Tri; Sudrajat, Agus Oman; Alimuddin (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Graphical Abstract Highlight Research Genus Nomorhamphusfrom three river inlets of Lindu Lake, Central Sulawesi was identified as Nomorhamphus with CO1 gene. Green wavelength can accelerate growth and maturation. Wild fish Nomorhamphus can complete life cycles in an aquaculture environment. Domestication level two is completed. Abstract Genus Nomorhamphus is an endemic fish that can be found in Sulawesi, Indonesia. This fish belongs to the halfbeak group and has diverse colors and morphology. It has economic value as an export commodity in the ornamental fish trade. Exploration of the genetic relationship of genus Nomorhamphus in Central Sulawesi is still limited. Nomorhamphus's fulfillment of export demand still comes from wild catches. This study aimed to identify the genetic relationship of genus Nomorhamphus in the inlet rivers of Lake Lindu, Central Sulawesi, and evaluate the adaptation response of genus Nomorhamphus to different wavelengths of light exposure. Caudal fin of six fish from the three inlet rivers of Lake Lindu were preserved in 95% ethanol for DNA extraction purposes. This research used a completely randomized design with three treatment, namely rearing under white (400 nm), green (525 nm), and red (625 nm) light for 60 days. Each treatment had three replications in the form of aquariums, with each aquarium being filled with four fish. A total of 42 fish were utilized in the study. CO1 sequence was amplified with universal primers of FISH-F2 and FISH-R2. The PCR amplification products were then sequenced and performed with phylogenetic tree analysis. The genetic diversity analysis suggests that the genus Nomorhamphus of all three rivers, Lindu Lake, Central Sulawesi is one species as Nomorhamphus sp.. Male and female growth length and gonad maturation were developed faster under green light exposure, while survival rate, blood glucose level, and color quality were not significantly different under different light. Exposure of wild fish to green light Nomorhamphus sp. can accelerate gonad maturation and growth to accelerate domestication.